The effect of ethical leadership on employees’ empowerment: Field study at Al- Azhar University in Assuit - Arab Republic of Egypt - Sewify, Abeer Mokhtar (Journal of Economic, Administrative and Legal Sciences, 2020)
Empowering employees is one of the recent administrative trends in human resource development, which is responsible for increasing productivity and improving quality and profitability in organizations. In order to permit the organization to achieve this, it needs to adopt an ethical leadership style that provides the appropriate climate to support the empowerment of workers. The study aimed to investigate the impact of ethical leadership on employees’ empowerment at Al- Azhar University in Assuit. The research problem of the current study was represented in the following inquiry: Does ethical leadership affects employees’ empowerment at Al- Azhar University in Assuit branch? The study relied on the descriptive-analytical approach. The researcher used Pearson correlation to measure the strength of association between the two variables of this study (ethical leadership and employees’ empowerment) and their dimensions and direction of the association. The researcher used simple regression analysis to test the hypotheses and relationships of the independent and dependent variables. The study sample included (317) people from Al- Azhar University where data was collected using a survey list prepared for the purpose of the study and only 255 questionnaires were received, rates about 80%. And the study reached several results; the most important of which is that the degree of exercise for the two study variables came with an average degree for each of them, where the average value for ethical leadership reached (3.57) and for employee empowerment the average was (3.53). Furthermore, it was found that there was a significant effect of ethical leadership behaviors on employees’ empowerment, as the value of (T) was (1.98), which is significant at the level of (0.01). The study recommended the need to support the values ​​of ethical leadership ​​and their basic dimensions through holding training courses and workshops to spread the tenet ​​of ethical leadership in the organization and its values as well. Last but not least, we recommend the organizations to adopt an effective system that permit them to monitor the application of the concept of employees’ empowerment.